1990
DOI: 10.2527/1990.68113588x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various levels of ractopamine hydrochloride on the performance and carcass characteristics of finishing swine.

Abstract: Six trials involving 888 pigs (Study 1) and three trials involving 360 pigs (Study 2) were conducted at various geographical locations in the U.S. and Canada to evaluate the effect of ractopamine hydrochloride on the performance and carcass characteristics of finishing swine. All trials were conducted using a randomized complete block design. Trial data were pooled within study for statistical analysis. Pigs averaged approximately 64.5 kg (Study 1) and 65.9 kg (Study 2) initially and had ad libitum access to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
87
4
21

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(126 citation statements)
references
References 5 publications
13
87
4
21
Order By: Relevance
“…This agrees with studies in which IMF increased in pigs fed RAC (10 ppm) and had CP (16 %) levels higher than those used here (16,35) . However, in other studies no changes in pork chemical composition were observed in pigs fed diets higher RAC and CP levels: 20 ppm RAC, 17 % CP (36) ; 10 ppm RAC, 16 % CP (37) ; 10 ppm RAC, 17 % CP (38) .…”
Section: Resultados Y Discusiónsupporting
confidence: 82%
See 3 more Smart Citations
“…This agrees with studies in which IMF increased in pigs fed RAC (10 ppm) and had CP (16 %) levels higher than those used here (16,35) . However, in other studies no changes in pork chemical composition were observed in pigs fed diets higher RAC and CP levels: 20 ppm RAC, 17 % CP (36) ; 10 ppm RAC, 16 % CP (37) ; 10 ppm RAC, 17 % CP (38) .…”
Section: Resultados Y Discusiónsupporting
confidence: 82%
“…En general, el efecto de incluir la RAC en la dieta, independientemente del nivel de lisina, fue el de aumentar 26 % la GIM sobre la dieta testigo (P<0.01); lo que coincide con otros resultados (16,35) , donde se observó un mayor contenido de GIM en la carne de cerdos suplementados con RAC (10 ppm) en dietas con 16 % de proteína cruda. Sin embargo, en otras investigaciones no se observaron efectos en la composición química de la carne de cerdos alimentados con dietas con más de 16 % de PC y con niveles más elevados de RAC (dieta con 20 ppm RAC y 17 % de PC) (36) ; (dieta con 10 ppm to 1.3 percentile units.…”
Section: Resultados Y Discusiónunclassified
See 2 more Smart Citations
“…O cloridrato de ractopamina (agonista β-adrenérgico), classificado como uma fenetanolamina, análogo estrutural das catecolaminas, epinefrina e norepinefrina, atua como modificador do metabolismo do animal e age como agente repartidor de nutrientes, pois tem a capacidade de redirecionar a distribuição normal de nutrientes em função do metabolismo da célula, promovendo efeitos profundos no crescimento e no metabolismo do músculo esquelético e do tecido adiposo, fazendo assim com que nutrientes utilizados para produção do tecido adiposo sejam usados para aumento da síntese proteíca (RICKS; BAKER; DALRYMPLE, 1984;WATKINS et al, 1990;ADEOLA;YOUNG, 1993;SMITH, 1998;WRAY-CAHEN, 2001;BRIDI et al, 2006 ZAGURY et al, 2002).…”
Section: Ractopaminaunclassified